A conductive liquid crystal via facile doping of an n-type benzodifurandione derivative1. Issue 13 (7th April 2015) - Zhao, Bin; Li, Chang-Zhi; Liu, Sheng-Qiang; Richards, Jeffrey J.; Chueh, Chu-Chen; Ding, Feizhi; Pozzo, Lilo D.; Li, Xiaosong; Jen, Alex K.-Y.
<x xml:space="preserve">Abstract</x> Liquid crystalline n-type molecular semiconductors exhibit interesting molecular order/charge-transport correlations, and allow n-doping with phosphonium salt to afford high conductivities.